The Effect Of Managerial Ownership And Firm Size On Earning Management - Dwi Urip Wardoyo; Leila Hasnah Rosydah; Putri Astari Angraini (CV. Ulil Albab Corp, 2022)
Earnings management is an action taken by company managers to manipulate the information in the financial statements by increasing or decreasing profits according to their objectives, as a result the financial statements presented are not in accordance with the actual situation. The purpose of this study was to determine the effect of Managerial Ownership and Company Size on Earning Management simultaneously or partially. The population in this study is the transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used purposive sampling method which resulted in 10 companies for 5 years so that 50 sample were obtained. The data analysis methods used in this research are quantitative methods and panel data regression analysis.